Design and fabrication of an organic/inorganic hybrid co-planar waveguide electro-optic modulator - Gao, Weinan; Sun, Jie; Sun, Xiaoqiang; Yan, Yunfei; Gao, Lei; Zhang, Daming (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
We have successfully designed and demonstrated a co-planar waveguide (CPW) Mach–Zehnder (MZ) electro-optic (EO) modulator using a strip-loaded waveguide structure. The hybrid material, easily synthesized by sol–gel process, with a large EO coefficient of r33 = 50 pm/V and a long- -term stability at 80 °C for 200 hours is selected as the active layer. A simple and easily fabricated strip-loaded waveguide structure is designed for utilizing the EO material and reducing the coupling loss with optical fiber. The optimized design principles of the efficient transmission for such a modulator are discussed. The measured half-wave voltage Vπ of 8.5 V for the MZ modulator is gained at 1550 nm and shows a good agreement with the simulating result.
Optica Applicata, Vol. 39, 2009, nr 3, s. 467-472
Keywords: optyka; organic/inorganic; electro-optic modulator; strip-loaded; Mach–Zehnder